LITERATURE STUDY: INTENSIVE CARE UNIT-TALK, A COMMUNICATION AID FOR MAINTENANCE INTUBATED INTENSIVE PATIENTS [KAJIAN LITERATUR: INTENSIVE CARE UNIT-TALK, SEBUAH ALAT BANTU KOMUNIKASI BAGI PERAWATAN PASIEN INTENSIF YANG TERINTUBASI] - Eva Chris Veronica Gultom (Universitas Pelita Harapan, 2019)
ICU-Talk technique is a development of Augmented Alternative Communication (AAC) method. This technique provides some features that are compiled with a database computerized. This database has a major vocabulary and vocabulary developed and is highly compatible with all patients. Systematic review to analyze the effectiveness of such devices and the like in communication in an intubated patient..Authors use some search keywords that are